2018
DOI: 10.1136/bmjopen-2017-017703
|View full text |Cite
|
Sign up to set email alerts
|

Should total calcium be adjusted for albumin? A retrospective observational study of laboratory data from central Norway

Abstract: ObjectivesAlbumin-adjusted total calcium is often used as a surrogate marker for free calcium to evaluate hypocalcaemia or hypercalcaemia. Many adjustment formulas based on simple linear regression models have been published, and continue to be used in spite of questionable diagnostic accuracy. In the hope of finding a more pure albumin effect on total calcium, we used multiple linear regression models to adjust for other relevant variables. The regression coefficients of albumin were used to construct local a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
41
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(46 citation statements)
references
References 24 publications
2
41
0
3
Order By: Relevance
“…On the contrary, another research group presented a similar concept but could not confirm that the addition of phosphate improved the adjusted calcium equation in renal failure patients. 27…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, another research group presented a similar concept but could not confirm that the addition of phosphate improved the adjusted calcium equation in renal failure patients. 27…”
Section: Discussionmentioning
confidence: 99%
“…Second, our diagnosis of hypocalcemia was based on total rather than ionized serum calcium. While albumin-concentrations were available in 97% of the patients, albumin-corrected total calcium only correlates moderately with ionized serum calcium in advanced CKD [ 26 ] and others have concluded that uncorrected calcium is not inferior to corrected calcium in HD patients [ 15 , 16 ]. Third, whereas short-term adjustments of dialysate calcium might not have been captured in severely hypocalcemic patients, data shown in Table 6 provides little evidence for any systematic trend towards higher dialysate calcium in those with hypocalcemia which is similar to our observations in EVOLVE [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…The main cohort for analysis was restricted to patients with normal uncorrected total serum calcium levels ≥ 2.1 mmol/L at time of cinacalcet initiation. In clinical practice, physicians use uncorrected or albumin-corrected calcium to evaluate hypocalcemia although data suggest that uncorrected is not inferior to corrected calcium [ 15 , 16 ]; therefore, sensitivity analyses were also carried out based with albumin-corrected calcium. Similar to previous studies, hypocalcemia was defined as mild (calcium 2.0− < 2.1 mmol/L), moderate (calcium 1.87− < 2.0 mmol/L), and severe (calcium < 1.87 mmol/L).…”
Section: Methodsmentioning
confidence: 99%
“…Plasma total calcium concentration is influenced by the plasma albumin level. Numerous algorithms have been developed to allow correction of plasma total calcium concentration with the plasma albumin level, but their reliability remains questionable [54][55][56]. In the present study, we excluded participants with potential causes for abnormal plasma albumin concentration, like patients with renal disease, diabetes, liver disease, or any severe acute or chronic illness, and did not use albumin correction for the plasma total calcium values.…”
Section: Discussionmentioning
confidence: 99%